Much Ado About Nothing? The Wage Effect of Holding a Ph.D. Degree But Not a Ph.D. Job Position - Giuseppe Lucio Gaeta; Giuseppe Lubrano Lavadera; Francesco Pastore (Institute for the Study of Labor (IZA), 2016)
This paper contributes to the literature on overeducation by empirically investigating its effects on wages among Ph.D. holders. We analyze data collected in 2009 by the Italian National Institute of Statistics (ISTAT) through a large cross-sectional survey of Ph.D. recipients that allowed us observing their work placement few years after the completion of their studies. We extend previous contributions by providing an analysis based on the identification of genuine overeducation as resulting from the interaction of respondents' assessments that concern the usefulness of their Ph.D. title in order to get and to carry out their current job. The potential endogeneity of self-reported genuine overeducation is corrected by using an instrumental variables approach where the provincial incidence of overeducation among those that share the same educational profile of respondents is used as instrument. Our results suggest that genuine over-education is particularly detrimental for individual wages. It leads to a wage penalty of about between 23% and 25%, more than twice bigger than average, a sizeable gap for the country's compressed wage structure. These results allow us to better understanding the effects of job-education mismatch and provide some useful insights into the evaluation of the career outcomes of doctoral graduates.
Keywords: C26; I23; I26; J13; J24; J28; 330; job-education mismatch; genuine overeducation; overskilling; job satisfaction; wages; Ph.D. holders